Studi Literatur: Peran Caregiver Untuk Peningkatan Perawatan Kesehatan Pada Pasien Demensia - Riskha Dora Candra Dewi; Kushariyadi (Puslitbang Sinergis Asa Professional, 2020)
The role of caregivers for dementia patients to improve health care is not yet optimal. Dementia patient care is an experience-based effort for complex dementia patients that can increase the psychological pressure of caregivers. The aim of the study was to determine the effectiveness of the caregiver's role in dementia patients to improve health care. Search strategies for English-language studies that are relevant to the topic are carried out using the ScienceDirect, SagePub, Springer databases limited from 2014 to 2020. The keywords used are